Analisis Usabilitas Pada Website iLab Universitas Gunadarma Menggunakan Metode Heuristic Evaluation - Ahmad Apandi (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2020)
Gunadarma University's independent laboratory (iLab) is one of the laboratories that provides convenience in providing information through the website. The ease of accessing the website cannot be separated from the website's usability. Good usability is very influential for website users and must be met. In this study, the method used is heuristic evaluation. Heuristic is an evaluation method used to find errors in interface design. Based on the measurement of the iLab website using the heuristic evaluation method by Nielsen, it was found that ten aspects studied got one and two values, which means that the iLab website has several deficiencies that do not cause a problem or in other words are not a problem and do not interfere with users when accessing the iLab website. The highest severity rating of 2.00 is in the aspect of helping user recognize, diagnose, and recover from errors.